TREATMENT TACTICS FOR SUBCOMPENSATED OSTEOARTHRITIS - Ashirov M.U; Dusmanov Farruxjon Orifjon o'g'li; To'raqulov Azizbek Eshmat o'g'li; Rahmatov Ozodjon (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Relevance: At the present stage, osteoarthritis is one of the most common joint pathologies. This disease occurs with high frequency among patients over 50 years old, but cases of osteoarthritis are increasingly observed in younger people. It is worth noting that a high percentage of elderly patients suffering from osteoarthritis have a number of concomitant diseases, which determines a significant level of comorbidity in these patients. The gold standard for the treatment of osteoarthritis stages III-IV is joint arthroplasty. It is known that after endoprosthetics, the functional activity of the contralateral joint is significantly reduced, which subsequently leads to knee replacement surgery on the originally intact limb [1]. Soinivaara T.A. et al. studied the bone mineral density (BMD) of the femur of the operated and contralateral limb among patients who underwent knee arthroplasty. A significant decrease in BMD was noted after joint arthroplasty, which plays a major role in patient therapy in the postoperative period.